Finishing half-breed holstein steers in confinement using rations containing chicken litter and sorghum grain - Pereira, Eurípedes A.; Von Tiesenhausen, Igor M.E.V.; Solomoni, Eduardo; Primo, Gilberto B. (Pesquisa Agropecuaria Brasileira, 2014)
Thirty half-breed holstein steers (316.6 kg) were randomly assigned to three supplementation treatments composed of seven supplementation periods. The concentrate consisted of 47% chicken litter, 46% sorghum grain, 5.4% triturate corn cobs, 0.8% corn silage ad libitum, and 0.8% dicalcium phosphate. The concentrate contained 83.82% DM, 14.51% CP, 60.72% TDN, 14.58% CF and 1.38% tannins (DM basis). DM digestibility of the silage was 51.36%. Daily liveweight gains per animal were 0.668, 0.779 and 0.857 kg; daily DM intake of concentrate and silage were 1.97 and 6.27 kg, 3.80 and 5.08 kg, 4.83 and 4.37 kg respectively for treatments 1, 2 and 3. The ratio of concentrate-silage DM consumed and efficiency of feed conversion were: 1:3.18 and 12.33, 1:1.34 and 11.40, 1:0.90 and 10.99 kg respectively for the three treatments. The carcass yields were 53.63, 54.12 and 54.92% respectively. Supplementary feeding did not affect animal response. The levels of chicken litter and sorghum had no effect on carcass and viscera quality. An economical study showed no advantages in increasing concentrate levels in the ration.